Victim Profile and Pattern of Thoraco-Abdominal Injuries Sustained in Fatal Road Traffic Accidents - Shetty, B Suresh Kumar; Kanchan, Tanuj; Menezes, Ritesh G; Bakkannavar, Shankar M; Nayak, Vinod C; Yoganarasimha , K (Journal of Indian Academy of Forensic Medicine, 2012)
The present research aims to highlight the pattern of thoraco-abdominal injuries sustained by the  victims of fatal road traffic accidents (RTA) in Manipal, South India. The study is an autopsy based  observation of thoraco-abdominal injuries in victims of fatal road traffic accidents during 1999 – 2003.  Road traffic accidents accounted for most of the injury related deaths (77%) during the study period. A  male preponderance (86%) was observed with a male-female ratio of 6:1. Individuals in the age group of  21 to 50 years formed the most vulnerable (83%) group. External thoracic injuries were more common  than internal thoracic injuries in the thoracic region. In the abdominal region, internal injuries were more  common than external injuries. Lungs (61%) and kidneys (23%) were the most commonly involved organs  in the thoracic and abdominal regions respectively. Majority of the victims were two wheeler occupants  (35%) followed by pedestrians (23%). The study indicates the pattern of thoraco-abdominal injuries  sustained along with the trend of road traffic accidents in the region.
Keywords: Thoraco-Abdominal Injuries; Road Traffic Accidents; Blunt Force Trauma